2022
DOI: 10.3390/agriculture12091443
|View full text |Cite
|
Sign up to set email alerts
|

Residues and Uptake of Soil-Applied Dinotefuran by Lettuce (Lactuca sativa L.) and Celery (Apium graveolens L.)

Abstract: Pesticides have been used for decades to protect agricultural products and increase productivity by controlling crop pests. However, the frequent application of pesticides on crops or soil leads to the accumulation of their residues in the environment, which will be subsequently absorbed by plants and finally translocated to edible parts. This study aimed to investigate the uptake of soil-applied dinotefuran and three major metabolites by lettuce and celery from the previous season’s applications and analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The residue behavior of methoxyfenozide and pymetrozine in Chinese cabbage was conducted for their risk assessment, demonstrating temperature-dependent dissipation, leading to low health risk [ 37 ]. The uptake of total soil-residual dinotefuran by lettuce has recently demonstrated that about a 24–28% level of initial concentration was translocated into leaves 30 and 60 days after treatment [ 38 ]. This high uptake ratio was explained by high water solubility and lower sorption to soil organics [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The residue behavior of methoxyfenozide and pymetrozine in Chinese cabbage was conducted for their risk assessment, demonstrating temperature-dependent dissipation, leading to low health risk [ 37 ]. The uptake of total soil-residual dinotefuran by lettuce has recently demonstrated that about a 24–28% level of initial concentration was translocated into leaves 30 and 60 days after treatment [ 38 ]. This high uptake ratio was explained by high water solubility and lower sorption to soil organics [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%